Association between inflammatory bowel disease and interleukins, chemokines: a two-sample bidirectional mendelian randomization study - Fang, Guojiu; Kong, Fanzhi; Zhang, Haiqing; Huang, Bin; Zhang, Jifa; Zhang, Xueli (Frontiers in Immunology, 2023)
Background: Mendelian randomization (MR) was used to evaluate the bidirectional causal relationship between inflammatory bowel disease(IBD) and interleukins(ILs), chemokines . Methods: Genetic instruments and summary data of five ILs and six chemokines were obtained from a genome-wide association study database, and instrumental variables related to IBD were obtained from the FinnGen Consortium. Inverse variance weighting (IVW) was used as the main MR analysis method, and several other MR methods including MR-Egger and weighted median were used to confirm the reliability of the results. Sensitivity analyses such as heterogeneity and pleiotropy were also performed. Results: The IVW method provided evidence to support that genetically predicted IL-16, IL-18, and CXCL10 significantly positively correlated with IBD, while IL-12p70 and CCL23 significantly negatively correlated with IBD. IL-16 and IL-18 had a suggestive association with an increased risk of ulcerative colitis (UC), and CXCL10 had a suggestive association with an increased risk of Crohn’s disease (CD). However, there was no evidence to support that IBD and two main subtypes (UC and CD) are associated with changes in the levels of ILs and chemokines. The results of the sensitivity analyses were robust and no evidence of heterogeneity and horizontal pleiotropy was observed. Conclusions: The present study showed that some ILs and chemokines affect IBD, but IBD and its main subtypes (UC and CD) have no effect on the level changes of ILs and chemokines.